La nic 41 y su influencia en la valoración de los activos biológicos de las florícolas, cantón Cayambe, período 2022 - Caiza Morales, Alexandra Nayeli (2024)
ABSTRACT: The objective of this research work was to analyze IAS 41 and its influence on the valuation of the biological assets of flower crops, Cayambe Canton, in the year 2022. The investigative study was based on an inductive method with a quantitative approach, a noninvasive design was used. experimental, the population of 36 flower growers from the Cayambe canton, a documentary and field investigation were applied which allowed obtaining the respective information, the techniques that were used were a survey and documentary review with the respective instruments that were the questionnaire and the data sheet. observation. The results that were obtained in the process of its accounting treatment were a loss due to the valuation of the biological asset for a value of 15,080.16 USD in the particular case of the flower company Floraroma S.A. The difference between the financial statements and IAS 41 is of 690,339.64 USD. Therefore, it is concluded that IAS 4 is very important and fundamental when valuing biological assets, facilitating comparability in the accounting practices of flower companies.